A novel model of light-induced middle cerebral artery occlusion and recanalization in mice - Emilia Conti; Antea Minetti; Lapo Turrini; Noemi Carlini; Cristina Sarti; Anna Maria Gori; Elena Sticchi; Betti Giusti; Cristina Spalletti; Marzia Baldereschi; Anna Letizia Allegra Mascaro; Francesco Saverio Pavone (Communications Biology)
Abstract Ischemic stroke caused by the abrupt interruption of blood flow is one of the leading causes of death and disability worldwide. Despite expanding reperfusion treatment indications, a significant proportion of patients (54.5%) experiences poor outcomes, regardless of successful recanalization, emphasizing the need for clinically relevant preclinical stroke models to better understand the mechanisms associated with effective reperfusion. Here, we develop and characterize a novel mouse model of light-induced recanalization following the photothrombotic occlusion of the distal branch of the middle cerebral artery (MCA). The recanalization provides a meaningful reduction of the infarct volume compared to non-recanalized mice. Moreover, the generalized motor impairment is less severe, as measured by the Neuro Deficit score. Ex vivo investigation highlights that light-mediated recanalization mitigates astrocyte complexity in the periinfarct cortex of recanalized mice. Moreover, light-induced recanalization reduces cerebral edema occurrence. Finally, the investigation of circulating biomarkers shows that our model of occlusion and recanalization of the MCA recapitulates the neuroinflammatory cascade of the acute phase of ischemic stroke.